PENGEMBANGAN E-LKPD BERBASIS CANVA SITE MATERI PECAHAN SISWA KELAS IV SEKOLAH DASAR - Lukman Hakim; Rida Fironika Kusumadewi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research was motivated by the use of conventional printed student worksheets (LKPD) in mathematics learning at grade IV of SD Negeri Muktiharjo Lor, which caused students difficulties in understanding the concept of fraction multiplication operations. This study aims to develop, determine the feasibility, and practicality of Canva Site-based E-LKPD on the topic of ordinary fraction multiplication for grade IV elementary school students. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The product developed is an interactive E-LKPD with a space theme accessible via a link and QR code. Product feasibility was assessed through validation by four validators (media, content, and language experts), yielding a score of 94% in the very valid category. Practicality was measured through teacher response questionnaires (94%) and student response questionnaires (90%), with an overall practicality average of 92% in the very practical category. Thus, the Canva Site-based E-LKPD on fraction multiplication is declared valid and practical for use in mathematics learning for grade IV elementary school students. ABSTRAK Penelitian ini dilatarbelakangi oleh penggunaan LKPD cetak konvensional dalam pembelajaran matematika di kelas IV SD Negeri Muktiharjo Lor yang menyebabkan siswa mengalami kesulitan memahami konsep operasi perkalian pecahan. Penelitian ini bertujuan untuk mengembangkan, mengetahui kelayakan, dan kepraktisan E-LKPD berbasis Canva Site pada materi perkalian pecahan biasa kelas IV sekolah dasar. Metode yang digunakan adalah Research and Development (R&D) dengan model ADDIE yang meliputi tahap Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Produk yang dihasilkan berupa E-LKPD interaktif bertema luar angkasa yang dapat diakses melalui tautan dan QR code. Kelayakan produk dinilai melalui validasi oleh empat validator (ahli media, materi, dan bahasa) yang menghasilkan persentase sebesar 94% dengan kategori sangat valid. Kepraktisan diukur melalui angket respon guru (94%) dan angket respon siswa (90%), dengan rata-rata kepraktisan keseluruhan sebesar 92% berkategori sangat praktis. Dengan demikian, E-LKPD berbasis Canva Site pada materi perkalian pecahan dinyatakan valid dan praktis digunakan dalam pembelajaran matematika kelas IV sekolah dasar.